Do poor health conditions lead to higher allocation of development assistance? - Katharina Stepping (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper analyzes the targeting of development assistance for health across countries in a multivariate regression framework, based on data from 22 bilateral donors to 160 recipients between 1990 and 2007. Donor characteristics, recipient characteristics and the donor-recipient-relationship are argued to be important determinants. The results show that health indicators influence the average allocation decision, but not to the same degree. HIV prevalence significantly increases aid receipts, while under-five mortality and maternal mortality are insignificant. The quality of the institutional environment in the recipient country, programmatic preferences of the donor and the relationship between donor and recipient also affect the average allocation pattern.
Keywords: F35; O15; O19; 330; Foreign aid; Assistance; Health; Aid policy; MDGs; Entwicklungshilfe; Ausländisch; Gesundheit; AIDS; Millennium Development Goals; Entwicklungsländer